Design and processing of drug delivery formulations of therapeutic deep eutectic systems for tuberculosis - Roda, Ana (2020)
Therapeutic deep eutectic systems (THEDES) emerged as alternative therapeutic agents that can enhance the bioavailability of the currently used active pharmaceutical ingredients. The use of THEDES in combination with supercritical CO2 has started to be explored to formulate drug delivery systems through green technology. This work aimed to develop THEDES-delivery systems for tuberculosis therapy, by encapsulating L-arginine-based THEDES in a lipidic matrix, through supercritical CO2 technology. From the phase equilibrium study of THEDES and CO2, PGSS was selected for THEDES encapsulation. Herein, THEDES encapsulation through PGSS was accomplished for the first time, with an average encapsulation efficiency of 75 %. The influence of the THEDES water-content in PGSS processing was also studied, suggesting no interference of the THEDES-water content in the formulation of the THEDES particles. Furthermore, the cell viability of the THEDES and the particles with THEDES encapsulated was measured in L929 fibroblasts and the systems prepared were non-cytotoxic.